2010
DOI: 10.1002/hep.23615
|View full text |Cite
|
Sign up to set email alerts
|

Use of Surveillance for Hepatocellular Carcinoma Among Patients With Cirrhosis in the United States

Abstract: Background Surveillance for hepatocellular carcinoma (HCC) in patients with cirrhosis is recommended but may not be performed. The extent and determinants of HCC surveillance are unknown. Methods We conducted a population-based US cohort study of those over 65 years of age to examine utilization and determinants of pre-diagnosis surveillance in patients with HCC who were previously diagnosed with cirrhosis. Patients diagnosed with HCC during 1994-2002 were identified from the linked Surveillance, Epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
350
6
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(376 citation statements)
references
References 35 publications
13
350
6
7
Order By: Relevance
“…(12,13) However, most studies evaluating HCC surveillance correlates have primarily focused on patient sociodemographic and clinical characteristics. (7,14) The effect of theory-based, patient-reported psychosocial factors on HCC surveillance completion has not been quantified. A better understanding of patient knowledge, attitudes, and barriers, particularly among low-income minorities, is crucial to develop and implement effective interventions to improve HCC surveillance rates.…”
Section: Conclusion-patientsmentioning
confidence: 99%
“…(12,13) However, most studies evaluating HCC surveillance correlates have primarily focused on patient sociodemographic and clinical characteristics. (7,14) The effect of theory-based, patient-reported psychosocial factors on HCC surveillance completion has not been quantified. A better understanding of patient knowledge, attitudes, and barriers, particularly among low-income minorities, is crucial to develop and implement effective interventions to improve HCC surveillance rates.…”
Section: Conclusion-patientsmentioning
confidence: 99%
“…Patients were approximately 4.5-fold and 2.8-fold, respectively, more likely to receive regular surveillance than those seen by a primary care physician only. 26 In a systemic review, surveillance rates were significantly higher among patients followed in subspecialty gastroenterology clinics compared to those followed in primary care clinics (51.7% vs. 16.9%, p < 0.001). 27 There has been a study conducted to understand failure rates in surveillance.…”
Section: Current Level Of Awareness About Hepatocellular Carcinoma Sumentioning
confidence: 96%
“…Among a population of roughly 1,800 cirrhotic patients in the SEER database with an eventual diagnosis of HCC between 1994 and 2002, Davila, et al found that a smaller percentage of black patients received any screening as compared to white patients (40.8% versus 53.3%) [10]. "Any screening" in this case was defined as ever having an AFP level measured or an abdominal ultrasound.…”
Section: Lower Hcc Surveillance Rates In African Americansmentioning
confidence: 99%
“…Black patients with cirrhosis receive less surveillance for HCC than other racial groups particularly nonHispanic Caucasians [10]. Perhaps as a consequence, African Americans have more advanced tumor stage at diagnosis and receive definitive surgical treatment less often than other racial groups.…”
Section: Introductionmentioning
confidence: 99%